Co-self-assembled nanoaggregates of BODIPY amphiphiles for dual colour imaging of live cells1. Issue 62 (11th August 2015) - Fan, Gang; Lin, Yao-Xin; Yang, Le; Gao, Fu-Ping; Zhao, Ying-Xi; Qiao, Zeng-Ying; Zhao, Qiong; Fan, Yun-Shan; Chen, Zhijian; Wang, Hao
<x xml:space="preserve">Abstract</x> Co-self-assembled vesicular nanoparticles of two structurally comparable amphiphilic boron-dipyrromethene (BODIPY) dyes with dequenchable dual colour fluorescence were prepared for ratiometric imaging of live cells.